#TITLE_ALTERNATIVE# - ABDULLAH (NIM : 15301069), HANIF
Sewerage system is an important supporting system for a municipal area and became a public necessity, so it need to be planned correctly and accurately to guarantee the system will be running without any problems. Computer program development in sewerage planning was conducted in order to make sewerage planning and dimensionering easier and faster to accomplish. As well as to increase calculation result accuracy level. To develop a computer program that could calculate the dimension of sewer correctly and accurately, a development has been conducted to generate some algorithms based on slope and diameter increment. Beside that, some algorithms based on the calculation of minimum slope and ground slope has been developed as well. From these developed algorithms, the advantages and the weaknesses from each algorithm were analyzed and then a further refinery and development effort was conducted in order to generate a final algorithm that could produce the best sewer dimensionering result. From the examination result and program verification could be concluded that the best computer algorithm was the algorithm based on diameter increment which used double logical statement, design velocity and flow comparison Qdesign/Qfull. The selected algorithm transformed into a computer program and have been used for sewer dimensionering process. But the aplication of this program limited only for non-extreme slope area.